PMP22 ROLE IN ASSESSING THE DEGREE OF DEMYELINATION IN DIABETIC POLYNEUROPATHY - Гриб, В. А.; Скрипко, Л. А.; Купновицька-Сабадош, М. Ю.; Чудовська, Л. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
This research is about study of the effect of immune factor sin the progress ion and severity of diabetic polyneuropathy (DPN) clinical manifestations, and of the myelin destruction degree of peripheral nerve sin patients with type 2 diabetes mellitus (DM). The study involved 62 patients with type 2 DM with symptomatic stages of DPN according to the classification of P.J. Dyck and P.K. Tomas (1999). Based on the results of ENMG there were the following results. In case of IIA and III stages of DPN the signs of mixed motor nerve lesion with axonopathy predominance were noted. In patients with IIB stage, the extensive damage to myelin was observed parallel with the intensification of axonal lesions. The dependence of antibodies level to peripheral myelin protein 22 (MP22), which is a marker of nerves demyelination degree, from the state of a cell and hum oral immunity was revealed. It was concluded that immune dysfunction could be considered one of the pathogenetic link of polyneuropathy due to autoimmune processes. In addition, as evidence there is the high level of PMP22 antibodies in patients with type 2 diabetes mellitus.